Burundi : Third Review Under the Extended Credit Facility Arrangement and Request for Modification of Performance Criteria-Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Burundi. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2013)
This paper analyzes Burundi's Third Review Under the Extended Credit Facility Arrangement and Request for Modification of Performance Criteria. Policy discussions in the program focus on measures to strengthen fiscal performance, which have been reflected in a revised 2013 budget, bolstering public financial and debt management. The report highlights that the macroeconomic outlook remains difficult, compounded by downside risks related to uncertainties in the external economic environment. Also, the need to preserve debt sustainability continues to anchor medium-term fiscal policy.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet